Hubungan Miopia dengan Skor IQ (Intelligence Quotient) pada Siswa SMP Negerti 1 Kota Padang - Jonas Hansel Tarigan; Muhammad Syauqie; Bobby Indra Utama (Jurnal Ilmu Kesehatan Indonesia, 2021)
Background. Myopia is one of the most common refractive errors. Refractive disorders indicate a relationship with IQ (Intelligence Quotient). It was first found to show that the higher the person's myopia the higher the IQ score he obtained.Objective. This study aims to determine the relationship between myopia and IQ scores in students of SMPN 1 Padang City.Method. This research is a comparative analytical study with a cross-sectional design using primary data and secondary data from May 2020 - August 2020 at SMPN 1 Padang. The sample consisted of 44 people with 22 people as cases and 22 people as controls. Data analysis used univariate analysis and bivariate analysis. The r value indicates the strength of the correlation and the results are statistically significant if the p value is <0.05.Result. The results showed that most of the respondents consisted of female students (52.3%), the incidence of myopia was found more in female students (72.7%), the highest degree of myopia was obtained by mild myopia (59.1%), the highest IQ score was obtained. with a high level of intelligence (65.9%) with a mean; myopia IQ score 117 ± 17.5, control IQ score 121.68 ± 16.3. In several bivariate analyzes, it was found that there was no relationship between myopia and IQ score (p> 0.05).Conclusion. In this study, there was no significant relationship between myopia and IQ score.